Transport of urea at low concentrations in Chlamydomonas reinhardi. - Williams, S K (1977)
Urea transport into the unicellular green alga Chlamydomonas reinhardi was investigated to further our understanding of controls operating on urea catabolism in this organism. Transport into cells grown with acetate and deprived of ammonia is a saturable process, mediated by at least two systems operating maximally at different external urea concentrations. The lower concentration system, with an apparent Km for urea of 5.1 micron, was the object of detailed study. Transport of urea from a saturating concentration (57 micron) into ammonia- and acetate-grown cells freshly suspended in ammonia-limited medium was not detected. Upon further culturing in the absence of ammonia, derepression occurred with transport ability, first appearing at about 1 h , reaching a maximum at about 2 h, and maintaining this maximum at least 5 h. In contrast to this, CO2-grown cells became derepressed more slowly, and maximum transport ability was not maintained. Addition of ammonia or methylamine (5 mM) during nitrogen deprivation prevented further increases in transport ability and caused loss of previously acquired transport ability. Cycloheximide (10 microng/ml) had a similar effect. Energy uncouplers or dark, anaerobic conditions depressed transport. By these criteria, transport from low urea concentrations is mediated by a process that requires protein synthesis and activation by cellular energy, and the process has a rapid rate of turnover and of deactivation by ammonia.